RESP: Relay suitability-based routing protocol for video streaming in vehicular Ad Hoc Networks - Hammood, Omar A.; M. N. M., Kahar; Mohammed, Muamer N. (Agora University, 2019)
Video streaming in Vehicular Ad Hoc Networks (VANETs) is a fundamental requirement for a roadside emergency and smart video surveillance services. However, vehicles moving at a high speed usually create unstable wireless links that drop video frames qualities. In a high-density network, network collision between vehicles is another obstacle in improving the scalability of unicast routing protocols. In this paper, the RElay Suitability-based Routing Protocol (RESP) which makes a routing decision based on the link stability measurement was proposed for an uninterrupted video streaming. The RESP estimates the geographic advancement and link stability of a vehicle towards its destination only in the small region. To ensure the reliability while extending the scalability of routing, the relay suitability metric integrates the packet delay, collision dropping, link stability, and the Expected Transmission Count (ETX) in the weighted division algorithm, and selects a high-quality forwarding node for video streaming. The experimental results demonstrated the proposed RESP outperformed the link Lifetime-aware Beacon-less Routing Protocol (LBRP) and other traditional geographical streaming protocols in providing a high packet delivery ratio and packet delay with various network densities, and proved the scalability support of RESP for video streaming.